Description of the Intramunicipal Habitat with Significant Concentrations of Foreign Population. The Case of the Province of Málaga (Spain) - Natera-Rivas, Juan Jose; Larrubia-Vargas, Remedios; Navarro-Rodríguez, Susana (Bulletin of Geography. Socio-economic Series, 2021)
The presence of foreigners in the province of Malaga is highly noticeable, especially in specific municipalities such as the city of Malaga, coastal areas, or villages in the Axarquia region. But from a geographical point of view, there are comparatively few investigations dedicated to the definition of the space in which foreign immigrants reside. The aim of this this research is to provide a description of the habitats where people who were born abroad tend to concentrate in the province of Malaga. The main novelty of the research is the scale of analysis we have used, the intramunicipal one, based on the Nomenclator statistics. This is specially relevant when we are dealing with small municipalities –in some of which the proportion of foreigners is quite high-, because is the only one that allow us to characterize the habitat of the foreingners.